Dermatopathology Round. A Cross‑sectional Study of Direct Immunofluorescence in the Diagnosis of Immunobullous Dermatoses. - Buch, Archana C.; Kumar, Harsh; Panicker, N. K.; Misal, Sonali; Sharma, Y. K.; Gore, Charusheela R. (Indian Journal of Dermatology)
Background: Autoimmune blistering diseases are a group of bullous disorders characterized by pathogenic antibodies directed at the target antigens, which are components of the desmosomes or adhesion complex at the dermoepidermal junction. Direct immunofluorescence (DIF) is invaluable in the diagnosis of these lesions. Aim: The aim of this study was to evaluate the sensitivity of DIF in immunobullous dermatoses and to study the pattern of DIF. The study also aims to correlate DIF with clinical and histologic findings and to analyze discrepancies. Materials and Methods: Total 100 biopsies received over a period of 2 years in the Department of Pathology were analyzed. DIF, histopathology and clinical data were reviewed. Results: Out of 100, 89 cases showed DIF patterns concordant with clinical/histologic diagnosis. The sensitivity of DIF was 94.44% (51/58) in the pemphigus and 84% (21/25) in the bullous pemphigoid (BP) group, 100% each in dermatitis herpetiformis (2/2) and linear IgA disease (1/1). A total of 11 histologically proven cases of immunobullous lesions were DIF negative-four (three of pemphigus vulgaris and one of BP) due to having no epidermis, three (cases of BP) owing to sampling/technical errors and the remaining four (cases of pemphigus vulgaris) due to being on treatment. Conclusion: Immunofluorescence helps confirm the diagnosis of bullous lesions in which there is clinical and the histopathologic overlap. Sampling errors contributed to false negative (FN) results.